Special type of pheromone-induced invasive growth in Saccharomyces cerevisiae - Frýdlová, Ivana; Basler, Marek; Vasicová, Pavla; Malcová, Ivana; Hasek, Jirí (Current genetics, 2007)
The ability to invade a solid substrate is an important phenomenon due to its connection with pathogenic activity of fungi. We report here on invasion displayed by MATalpha cells of Saccharomyces cerevisiae lacking Isw2p, a subunit of the ISW2 chromatin remodelling complex. We found that on minimal medium, where the isw2Delta MATalpha mutant is not invasive, additional absence of another ISW2 complex subunit, Dls1p or Dpb4p, promoted invasion. Our microarray data showed that derepression of MAT a-specific genes caused by absence of Isw2p is very low. Their expression is increased only by the autocrine activation of the mating pathway. Invasion of isw2Delta MATalpha cells thus resembles the pheromone-induced invasion, including dependence on Fig2p. We show here that another pheromone-induced protein, mating agglutinin Aga1p, can play a role in the agar adhesion necessary for invasion. In contrast with MAT a-cells invading agar under low alpha-pheromone concentration, the invasive growth of isw2Delta cells specifically requires Fus3 kinase. Its function in the invasion of isw2Delta MATalpha cells cannot be completely substituted by Kss1 kinase, which plays a basic role in invasive growth signalling. We suggest that partial dependence of the isw2Delta MATalpha invasion on Fus3p and Aga1p corresponds to a weaker pheromone response of this mutant.
Keywords: Saccharomyces cerevisiae; jaderné proteiny; signální transdukce; MAP Kinase Signaling System; Up-Regulation; Gene Deletion; Nuclear Proteins; upregulace; Signal Transduction; Saccharomyces cerevisiae Proteins; geny hub; Saccharomyces cerevisiae - proteiny; Transcription Factors; proteinové prekurzory; Models, Biological; Protein Precursors; transkripční faktory; Mitogen-Activated Protein Kinases; delece genu; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; biologické modely; mitogenem aktivované proteinkinasy; MAP kinasový signální systém; Adenosine Triphosphatases; Oligonucleotide Array Sequence Analysis; Genes, Fungal; molekuly buněčné adheze; adenosintrifosfatasy; Cell Adhesion Molecules